2020
DOI: 10.3390/genes11050524
|View full text |Cite
|
Sign up to set email alerts
|

Genotype-Phenotype Correlation: A Triple DNA Mutational Event in a Boy Entering Sport Conveys an Additional Pathogenicity Risk

Abstract: The purpose of this paper is to present a clinical and laboratory study of a family, in which a 12-year-old boy was examined to assess his health status before starting competitive sports. A variety of clinical and instrumental tests were used to evaluate the status of the heart and its functions. Using Sanger sequencing (SS), we sequenced six related genes to verify suspected arrhythmogenic right ventricular cardiomyopathy (ARVC) hypothesized at the cardiac assessment and, subsequently, by a next-generation s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…Arrhythmogenic cardiomyopathy (ACM) is a heart muscle disease characterized by a fibro-fatty replacement of the right ventricular and/or left ventricular myocardium, which leads to anatomical, contractility and electrical rhythm abnormalities with life-threatening complications [18,19]. The predominant cause of the dominant-right ACM (ARVC) is represented by mutations in genes that encode components of desmosomes, the adhesive junctions that connect cardiomyocytes, and it leads to the loss of efficient electrical coupling with a consequent increased arrhythmic burden [20].…”
Section: Arrhythmogenic Cardiomyopathymentioning
confidence: 99%
“…Arrhythmogenic cardiomyopathy (ACM) is a heart muscle disease characterized by a fibro-fatty replacement of the right ventricular and/or left ventricular myocardium, which leads to anatomical, contractility and electrical rhythm abnormalities with life-threatening complications [18,19]. The predominant cause of the dominant-right ACM (ARVC) is represented by mutations in genes that encode components of desmosomes, the adhesive junctions that connect cardiomyocytes, and it leads to the loss of efficient electrical coupling with a consequent increased arrhythmic burden [20].…”
Section: Arrhythmogenic Cardiomyopathymentioning
confidence: 99%
“…Here, we report a non-severe, familial case of non-obstructive HCM, associated with mild clinical features of NS, diagnosed by a multidisciplinary team of expert cardiologists and geneticists. Cardiac and non-cardiac red flags (RF) represent important diagnostic markers that permit to suspect a specific cause of cardiomyopathy and a distinction between sarcomeric and non-sarcomeric types [ 1 , 3 ], and genetic testing represents a necessary diagnostic tool for performing a definitive etiological diagnosis [ 15 , 16 , 17 , 18 ]. Indeed, the association between HCM and pulmonary stenosis and/or dysmorphisms should always raise suspicion of genetic syndromes, even in adults.…”
Section: Discussionmentioning
confidence: 99%
“…Twelve publications, ranging from 2008 to 2020, were found, meeting the above-mentioned eligibility criteria, in principle. Seven papers depicted eight single case reports of athletes of Caucasian origin [ 39 , 40 , 41 , 42 , 43 , 44 ]. However, we excluded three among seven, because they did not report technologies used to perform genetic test and/or the specifications of the identified genetic variants [ 39 , 40 , 41 ].…”
Section: Diagnostic Yield Of Genetic Testing In Athletesmentioning
confidence: 99%
“…However, we excluded three among seven, because they did not report technologies used to perform genetic test and/or the specifications of the identified genetic variants [ 39 , 40 , 41 ]. The remaining are four case reports of white, asymptomatic, amateur athletes, who showed ECG anomalies during the pre-participation screening requiring a thorough cardiac evaluation in tertiary referral centres ( Table 2 ) [ 24 , 42 , 43 , 44 ]. Of note, an athlete reported that two relatives died suddenly at a young age [ 44 ].…”
Section: Diagnostic Yield Of Genetic Testing In Athletesmentioning
confidence: 99%
See 1 more Smart Citation